IMPLEMENTASI PROGRAM PRIORITAS DALAM PENGELOLAAN ADMINISTRASI KAMPUNG DI DISTRIK MULIA KABUPATEN PUNCAK JAYA (Studi Implementasi Permendagri No. 47 Tahun 2016 tentang Administrasi Pemerintahan Desa) - David W. Telenggen; Nur Aedah; Vince Tebay (JURNAL KEBIJAKAN PUBLIK, 2020)
This article aims to analyze the implementation of priority work programs in Village Administration Management in Mulia District, Puncak Jaya Regency. And then analyze the factors that hinder the implementation of priority work programs in Village Administration Management in Mulia District, Puncak Jaya Regency. And then analyze the efforts made in implementing priority work programs in Village Administration Management in Mulia District, Puncak Jaya Regency The research method: is a qualitative descriptive with 12 informants, observation collection techniques, interviews and literature study. The analysis techniques are data display, reduction, grouping and conclusions. The results of the study: first, the implementation of priority work programs in Village Administration Management in Mulia District, Puncak Jaya Regency is quite good. such as in communication, outreach has been made to the Village Government in District meetings. To provide explanations related to priority work programs in village administration specifically in population administration. The resources are sufficient, then the disposition in each village has been arranged to be able to support the implementation of the program even though it is not optimal. Then the bureaucratic structure has been implemented quite well. Second, the factors that hinder the implementation of priority work programs in Village Administration Management in Mulia District, Puncak Jaya Regency, namely the problem of human resources that is still lacking, besides that communication problems that cannot be understood by village officials make the implementation of priority programs not running optimally. Apart from that, the bureaucracy structure is less efficient and less dynamic. Third, Efforts made in implementing priority work programs in Village Administration Management in Mulia District, Puncak Jaya Regency by conducting training, guidance as well as formal and informal education for village officials to increase the knowledge of village officials. In terms of bureaucratic structure, there are efforts to improve the existing structure in coordination with the District Government of Mulia, Puncak Jaya Regency.